2004
DOI: 10.1038/sj.onc.1208242
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signature for angiogenic and nonangiogenic non-small-cell lung cancer

Abstract: Angiogenesis is regarded as essential for tumour growth. However, we have demonstrated that some other aggressive non-small-cell lung carcinomas (n-SCLC) do not have angiogenesis. In this study, using cDNA microarray analysis, we demonstrate that angiogenic and nonangiogenic tumour types can be distinguished by their gene expression profiles. Tissue samples from 42 n-SCLC patients were obtained with consent. In all, 12 tumours were nonangiogenic and 30 angiogenic. The two groups were matched by age, sex, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 17 publications
3
73
0
Order By: Relevance
“…Owing to hypoxic events that frequently occur during cancer cell progression, genes such as those governing efficient regulation of oxygen homeostasis could be properties clonally coselected for by evolving cancer cells (Pugh and Ratcliffe, 2003). This suggestion is supported by Hu et al (2005) who have described finding higher levels of genes coding for proteins involved in mitochondrial metabolism in nonangiogenic tumours. It is also known that clonal chromosomal changes found in malignant tumours have a strong correlation with tumour morphology (Gisselsson et al, 2001;Gisselsson, 2002).…”
Section: Discussionsupporting
confidence: 67%
“…Owing to hypoxic events that frequently occur during cancer cell progression, genes such as those governing efficient regulation of oxygen homeostasis could be properties clonally coselected for by evolving cancer cells (Pugh and Ratcliffe, 2003). This suggestion is supported by Hu et al (2005) who have described finding higher levels of genes coding for proteins involved in mitochondrial metabolism in nonangiogenic tumours. It is also known that clonal chromosomal changes found in malignant tumours have a strong correlation with tumour morphology (Gisselsson et al, 2001;Gisselsson, 2002).…”
Section: Discussionsupporting
confidence: 67%
“…This suggests that the expression of TSP-1 is very important in tumour invasion; a high expression of TSP-1 may play an important An inverse correlation between TSP-1 expression and microvessel density was found for squamous cell carcinoma but no correlation was found for adenocarcinoma, which is consistent with the results of Yamaguchi et al 6 This strongly suggests that the mechanism of tumour inhibition by TSP-1 differs according to histological type in terms of TSP-1 suppressing the development of squamous cell carcinoma through inhibiting tumour angiogenesis, although in adenocarcinoma another type of inhibition may be occurring. Hu et al 12 reported that no neovascularization occurred in the tumour in some NSCLC cases, with tumour development and progression depending entirely on tumour cell proliferation. It has also been reported that TSP-1 can act by directly inhibiting tumour proliferation, without neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected finding was instead the increased expression in non-angiogenic tumours of a set of genes linked to Oxidative Phosphorylation, suggesting the possibility of metabolic reprogramming in the nonangiogenic tumours. The second finding was the decreased level, in the same tumours, of a set of adhesion molecule genes, raising the hypothesis that diminished cell to cell contact might be associated with failure to develop a vascular infrastructure [43].…”
Section: Non-angiogenic Growth: Why Does It Happen?mentioning
confidence: 99%
“…No differences in microvessel density and apoptosis were observed [12]. An immunohistochemical study failed to demonstrate any major difference in the expression of markers of angiogenesis and hypoxia, the only exception being stromal thrombospondin that was almost absent in non-angiogenic but widely present in angiogenic tumours [12,13] possibly because of its anti-angiogenic activity plays a role in the vascular re modelling occurring in angiogenic cancers [43]. mRNA expression profiling by microarray studies confirmed that no differences in classic hypoxia or angiogenesis pathways could be found with the exception, again, of Thrombospondin1.…”
Section: Non-angiogenic Growth: Why Does It Happen?mentioning
confidence: 99%